-x^2-7x=-11
x^2 - 7x = 11
x^2 - 7x + 49/4 = 11 + 49/4
(x - 7/2)^2 = 44/4 + 49/4
x - 7/2 = ± √93/2
x = (7 ±√93)/2
Complete the square to Solve Quadratic Equation:
Solve the equation. Express the answer in simplest radical form.
-x^2-7x=-11
Please Help!!!! Thanks.
5 answers
Thank you so much, but I was wondering:
-x^2-7x=-11
x^2 - 7x = 11
You have to divide by -1, wouldn't it be positive 7x.
-x^2-7x=-11
x^2 - 7x = 11
You have to divide by -1, wouldn't it be positive 7x.
YOU ARE RIGHT!
good for you for catching that.
I am sure you can make the necessary changes.
(there is one small change)
good for you for catching that.
I am sure you can make the necessary changes.
(there is one small change)
This is not a trigonometry question.
x^2 + 7x + (7/2)^2 = 11 + (7/2)^2
(x + 7/2)^2 = 23 1/4
x = -7/2 +/- sqrt(93)/2
x^2 + 7x + (7/2)^2 = 11 + (7/2)^2
(x + 7/2)^2 = 23 1/4
x = -7/2 +/- sqrt(93)/2
Thank you so much!!!!
Could you please help me with another type of trig math question. I greatly appreciate your help.
Could you please help me with another type of trig math question. I greatly appreciate your help.